Framing Improvement of Emergency Services RSKJ Soeprapto Hospital with Lean and WAM Modification - Erlina Puspitaloka Mahadewi; Ade Heryana; Fori Yumita; Mulyo Wiharto; Lia Amalia (International Journal of Science, Technology & Management, 2021)
The present study reports the first comprehensive research on covid19 emergency services model. Healthcare services inside hospitals during pandemic can apply the Lean Hospital and Waste Assessment Model (WAM) modification, which is a new method that can be used to identify waste in the hospital service process flow and operational of emergency service. The purpose of this study is to provide recommendations for improving emergency services in the covid19 era. The method used in this research is a descriptive qualitative analysis carried out through observing the service flow of patients who will be hospitalized from the emergency, confirming the service flow by in-depth interviews and looking at secondary data and giving a questionnaire on a modification of eight waste relationship at 15 persons expert who understands the emergency service process. The results showed that the critical waste of emergency services at RSKJ Soeprapto hospital is a waste of human skills of 17.5%. The reasons for the emergence above are because the covid19 team has not yet been formed, the absence of special officers to conduct primary triage before the patient enters the emergency unit, and many officers who do not understand the flow of emergency services in the covid19 pandemic era. In order to improve hospital services in the future, it is necessary to form a covid19 team, to develop a standard emergency service guide, to conduct continuous socialization to all the hospital staff through education and training programs, which are recommendations for improving emergency services at RSKJ Soeprapto Hospital Bengkulu in the pandemic era and new normal preparation.